Umbilical cord-derived secretome induces apoptosis and reduces proliferation in cancer cells - Awan, Sana Javaid; Manuwar, Maliha; Shahzadi, Mubeen; Hafeez, Sana; Kausar, Humera (International Journal of Applied and Experimental Biology, 2025)
Umbilical cord mesenchymal stem cells (UCMSCs) have the best ability to travel to the tumor site and they serve as a tool to fight cancer. This study showed that secretome from UCMSCs (UCMSCs-Sec) could inhibit the growth of prostate cancer (PC-3) and cervical cancer (HeLa) cells, and induce apoptosis in the cells. The UCMSCs-Sec treatment was given to PC-3 and HeLa cells. After 7 days, cell viability assay was performed to evaluate cell viability, and ELISA for vascular endothelial growth factor (VEGF) was performed to evaluate neovascularization. RT-PCR was also done to measure the expression of ki67, caspase-3, PCNA, BAX and GAPDH genes. The levels of secreted antioxidative enzymes, including superoxide dismutase, ascorbate peroxidase, catalase, and glutathione, were estimated in the treated and untreated groups. Decreased cellular viabilty revealed increased apoptosis in HeLa and PC-3 cells treated with UCMSCs-Sec. Gene expression analysis showed that apoptotic genes (BAX and caspase-3) were upregulated, proliferative genes including ki67 and PCNA were reduced, while GAPDH remained unchanged as it is a house-keeping gene. The UCMSCs-Sec treatment was also found to reduce neovascularization in the cancer cells. Furthermore, relative levels of secreted antioxidative enzymes were also reduced in PC-3 and HeLa cells treated with UCMSCs-Sec. These findings could be an indicative that UCMSCs-Sec can promote cellular death and prevent the cellular division of cancer cells. The present study explores anticancer potential of secretome from USMSCs. This strategy could be a viable therapeutic option for the treatment of neoplastic cells.